2018
DOI: 10.3892/or.2018.6904
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑98/PTEN/AKT pathway inhibits cell proliferation and malignant progression of hypopharyngeal carcinoma by MTDH

Abstract: Laryngeal carcinoma is one of the most common tumors concerning otorhinolaryngology head and neck surgery, however, the pathogenesis of laryngeal carcinoma remains unclear. MicroRNAs (miRNAs) have been reported to play vital roles in the pathogenesis of laryngeal carcinoma Herein, the present study was designed to explore the function and mechanism of miRNA-98 in hypopharyngeal carcinoma. In brief, qRT-PCR, MTT assay, western blot analysis, Transwell assay and luciferase reporter assay were performed. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Some studies have uncovered the involvement of MTDH in the regulation of the PTEN-AKT signaling pathway. 23,24 We determined whether miR-559 inhibits the output of the PTEN-AKT pathway in GBM cells. MiR-559 mimics and pcDNA3.1 or pcDNA3.1-MTDH were introduced into U251 and T98 cells, and western blot analysis was performed to measure MTDH, p-AKT, and AKT protein amounts.…”
Section: Mir-559 Inhibits Akt In the Pten-akt Pathway In Gbm Cellsmentioning
confidence: 99%
“…Some studies have uncovered the involvement of MTDH in the regulation of the PTEN-AKT signaling pathway. 23,24 We determined whether miR-559 inhibits the output of the PTEN-AKT pathway in GBM cells. MiR-559 mimics and pcDNA3.1 or pcDNA3.1-MTDH were introduced into U251 and T98 cells, and western blot analysis was performed to measure MTDH, p-AKT, and AKT protein amounts.…”
Section: Mir-559 Inhibits Akt In the Pten-akt Pathway In Gbm Cellsmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) has been appreciated as an important tumor suppressor and to oppose phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway in human cancers [12]. Accruing works have revealed that PTEN is involved in progression of cancers and negatively correlated with AKT signaling in hypopharyngeal carcinoma, non-small cell lung cancer and esophageal squamous cell carcinoma [13][14][15]. Previous study suggested that loss of PTEN is associated with progression of papillary thyroid cancer [16].…”
mentioning
confidence: 99%
“…However, the regulatory mechanism of MTDH is diverse. Studies have reported that several miRNAs, such as miR-98, miR-182-5p, miR-36645p and miR-384, could exert antitumour effects by targeting MTDH [36][37][38][39] . Sarkar et al 40 revealed that MTDH acted as a bridging factor by connecting NF-κB and CREB binding protein in malignant gliomas.…”
Section: Discussionmentioning
confidence: 99%